2022
DOI: 10.3389/fped.2022.997834
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy of emergency management of domestic helpers in pediatric home accidents: A cross-sectional survey in Hong Kong

Abstract: BackgroundAccidental injuries are the leading cause of deaths and disabilities in children globally and most of them occur at home. To save life and prevent sequelae, domestic helpers (DHs) require providing emergency management (i.e., first aid) to children involved in home accidents. However, their self-efficacy in emergency management for children is rarely investigated. Hence, this study aimed to tap that research gap.MethodsThis study adopted a cross-sectional descriptive survey design. A convenience samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…It has the highest percentage among the answers to the questions in the questionnaire. The results of the study are similar to the results of the previous studies [13,14,16]. In Turkey, people used to call 110 for a fire, 112 for an ambulance, 122 for a disaster or emergency, 155 for police, 156 for gendarmerie, 177 for forest fires, and 158 for coast guard before 2021.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It has the highest percentage among the answers to the questions in the questionnaire. The results of the study are similar to the results of the previous studies [13,14,16]. In Turkey, people used to call 110 for a fire, 112 for an ambulance, 122 for a disaster or emergency, 155 for police, 156 for gendarmerie, 177 for forest fires, and 158 for coast guard before 2021.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, it is seen that the mothers have the lowest self-efficacy score in administering CPR to the child and they feel themselves inadequate in this regard. The results of the study are similar to those of [13,16]. In the study [17] in England with parents of 3-12 month-old infants, the first-aid self-efficacy rate of parents is 16.4%, while their self-efficacy in CPR is 15.7%.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In fact, experience with domestic accidents could be the main reason for improved mothers' knowledge. This has been reported by some authors, such as [7,28], although the study by Ho et al [29] showed no association between previous domestic accidents and mothers' level of knowledge. Another good explanation might be that mothers who have already brought another child involved in a domestic accident to a health center have learned the right attitudes and the ones to avoid, consequently increasing their knowledge scores.…”
Section: Factors Associated With Mothers' Knowledgementioning
confidence: 54%